Comparison Encryption of How to Work Caesar Cipher, Hill Cipher, Blowfish and Twofish - Haryono, Wasis (Data Science: Journal of Computing and Applied Informatics, 2020)
Security is the level of confidentiality of data stored using cryptography. There are many ways you can do to improve security. In this study, the writer will use a method by encrypting the database with the Caesar Cipher Algorithm, Hill Cipher and Blowfish. Caesar Cipher, Hill Cipher and Blowfish are part of the symmetric algorithm, which means that the encryption and decryption process have the same key. The encryption and decryption process in Caesar Cipher, Hill Cipher and Blowfish Algorithms each has one key. algorithm encryption techniques using symmetric passwords have 2 types, namely block ciphers and stream ciphers. Caesar Cipher, Hill Cipher and Blowfish and Twofish Algorithms are the encryption of the block cipher that breaks or creates blocks to encrypt and obtain cipher text. Result in this paper In Caesar Cipher, it is carried out like 3 blocks of encryption. Whereas in Hill Cipher a word is divided into several blocks and each block is encrypted. In Blowfish, several iterations are performed to get the text cipher, the input is 64 bits of data that can be done as many as 16 iterations. In Twofish the input is 128 bits, in contrast to Blowfish which is only 64 bits, Twofish can also accept 256 bits long and do 16 iterations to get the cipher text. Twofish has stronger security than the 3 algorithms above, Twofish also takes up more memory and takes longer to encrypt.